Genotype x environment interactions in an exotic commercial egg strain and the local chicken of Nigeria - Osu, A.; Dettmers, A. (Faculty of Agriculture, University of Ife, 2015)
Six hatches of the Apollo, a commercial egg strain of chicken imported from the United Kingdom at day old and the Local chicken hatched from eggs collected all over Southwestern Nigeria were reared under modem brooding, feeding and management conditions to study genotype, x environment interaction. Body weight, egg weight and egg production from first egg to eight months of production were recorded for each hen. Analyses of variance showed that there were significant breed x hatch interactions for age at sexual maturity, egg weight from the third month of production. and four and eight month egg production. Body weight at 12 and 20 weeks of age, weight of first egg and egg weight at first month of production did not show significant breed 5 hatch interaction effects. The results show that locally adapted breeds and strains are required, in view of large environmental differences between the temperate and tropical climates.